Analysis of Bandwidth Management Using Hierarchical Token Bucket and Layer 7 Methods - Ahmad Syofian; Sumarlin; Meiliyani Br Ginting (Karya Techno Solusindo, 2025)
For bandwidth regulation on the internet network at PABAKU Stabat Private Vocational Schools, it is carried out by managing bandwidth using the Hierarchical Token Bucket method. Hierarchical Token Bucket is a method that is created hierarchically and divided into several classes or levels consisting of parent and child, so that it can optimize bandwidth by limiting download and upload ratings for clients, and can determine the priority of bandwidth sharing on clients. Bandwidth management will also affect QoS (Quality of Service) to ensure quality of service in the network. Layer 7 Protocol on Mikrotik routers is a very good firewall in limiting internet access, which is done by adding a regexp to block sites such as social media sites (Facebook, Instagram, TikTok, Youtube, Detik) and other sites that are inefficient during the learning process in the computer laboratory, because they interfere with students' concentration on learning. REFERENCES Al Kautsar, D., & Nulhakim, L. (2020). Pengelolaan management bandwidth dengan menggunakan metodesimple queue di Toko Subur Graphic Jakarta Pusat. Jurnal Teknik Informatika STMIK Antar Bangsa,2(1).Daulay, O. L. (2020). Analisis quality of services (QoS) pada manajemen bandwidth menggunakan metodehierarchical token bucket (HTB) pada sistem jaringan. JISTech (Journal of Islamic Science andTechnology), 5(2).Husnaini, M., Bagye, W., & Ashari, M. (2019). Implementasi fitur Layer 7 protocols Mikrotik RB750 diSMKN 1 Narmada. Jurnal Informatika dan Rekayasa Elektronik, 2(1).https://doi.org/10.36595/jire.v2i1.94Ichwan, M. I., Sugiyanta, L., & Yunanto, P. W. (2019). Analisis manajemen bandwidth hierarchical tokenbucket (HTB) dengan Mikrotik pada jaringan SMK Negeri 22. PINJayanti, R., Rachman, S., & Irfan, L. A. S. (2020). Management bandwidth dan analisis QoS menggunakanmetode hierarchical token bucket (HTB) pada topologi star. Repository Universitas Mataram.Kurniawan, B., & Panjaitan, F. (2023). Pemanfaatan fitur Layer 7 protocol untuk filter website danmanajemen bandwidth. Jurnal Jupiter, 15(1).Pratomo, A. B. (2023). Pengembangan sistem firewall pada jaringan komputer berbasis Mikrotik RouterOS.Bulletin of Network Engineer and Informatics, 1(2). https://doi.org/10.59688/bufnets.v1i2.10Putra, K. G. W. P., Santyadiputra, G. S., & Kesiman, M. W. A. (2020). Penerapan manajemen bandwidthmenggunakan metode hierarchical token bucket pada layanan hotspot Mikrotik Undiksha. CESS (Journalof Computer Engineering, System and Science), 5(1). https://doi.org/10.24114/cess.v5i1.14959Rahmat, E., Hulu, J., Naibaho, J. F., & Purba, M. J. (2023). Perancangan dan implementasi manajemenbandwidth dengan metode hierarchical token bucket dan limitasi akses internet menggunakan Layer 7protocol pada router Mikrotik di SMP Negeri 1 Balige. Methotika.https://ejurnal.methodist.ac.id/index.php/methotikaSari, I. P., Siska, S. T., & Budiman, A. (2021). Perancangan aplikasi pelayanan gangguan TV kabel berbasisweb dan SMS gateway. Jurnal Pusat Akses Kajian Teknologi Artificial Intelligence, 1(1).Shomad, A., Akbar, Y., & Mulyana, D. I. (2022). Implementasi pembatasan akses sosial media menggunakanLayer 7 protocol pada perangkat Mikrotik di SMK IDN. Informatics for Educators and Professional:Journal of Informatics, 7(1). https://doi.org/10.51211/itbi.v7i1.1998Simarmata, H. S., & Widiasari, I. R. (2023). Manajemen bandwidth menggunakan hierarchical token bucket(HTB) (Studi kasus: PT Orion Cyber Internet). Technomedia Journal, 8(2SP).https://doi.org/10.33050/tmj.v8i2sp.2078Syahputri, C. N., Anggraini, C., Anugerah, H. F., Zufria, I., & Nahwi, M. I. (2023). Penerapan kinerja filterrule dengan metode raw dan Layer 7 protocol di router Mikrotik. Jurnal Kridatama Sains dan Teknologi,5(2). https://doi.org/10.53863/kst.v5i02.969Widiyaningrum, I. (2020). Rancangan sistem jaringan LAN (local area network) di satuan kerja staf operasiMabesau. Jurnal Online Mahasiswa Sistem Informasi dan Manajemen Informatika, 2.